ANALISIS KEBUTUHAN PENGEMBANGAN MODEL PEMBELAJARAN KETERAMPILAN MENULIS BAHASA ARAB BERBASIS DATA SCIENCE - Ihwan Rahman Bahtiar; Samsi Setiadi; Muhammad Kamal bin Abdul Hakim (JURNAL EDUSCIENCE, 2022)
This study aims to identify the needs of students in the Arabic Language Education Study Program, Faculty of Language and Arts, Jakarta State University for data science skills and their integration into learning writing skills. The research was conducted in June 2022 at Jakarta State University's Arabic Language Education Study Program. The study sample consisted of 30 students. The data collection technique used in this needs analysis is a survey technique. A questionnaire was used as a research tool, which was compiled and distributed via the Google form platform. The data analysis technique used is descriptive statistical analysis. Based on the results of the validity and reliability test, it was determined that the questionnaire used for data collection had valid and reliable items. The results of the data analysis show that the majority of students need and desire the teaching of data science skills that are integrated into learning Arabic writing skills.